2017
DOI: 10.1080/14992027.2017.1321788
|View full text |Cite
|
Sign up to set email alerts
|

Transient evoked otoacoustic emissions in rock musicians

Abstract: Our results suggest an incipient hearing loss at 6 kHz in rock musicians. Loss of TEOAE SNR in the 4 kHz half-octave frequency band was observed, but it was related to higher mean 3-6 kHz hearing thresholds and age. A large proportion of rock musicians have permanent tinnitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
5
0
3
Order By: Relevance
“…The frequencies generated by the instruments played is a key factor when assessing the risk of developing HL for PMs [ 27 ]; therefore, the musical genre may affect the characteristics of sounds PMs are exposed during practice [ 27 ]. Previous studies have shown that PR PMs are exposed to sounds of higher intensity compared to CL PMs, both during rehearsals and live performance [ 31 ], with an average exposure of 103 dB in PR versus 94 dB in CL PMs [ 27 ]; additionally, studies have described that PR PMs often play music without ear protection more commonly than CL PMs [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequencies generated by the instruments played is a key factor when assessing the risk of developing HL for PMs [ 27 ]; therefore, the musical genre may affect the characteristics of sounds PMs are exposed during practice [ 27 ]. Previous studies have shown that PR PMs are exposed to sounds of higher intensity compared to CL PMs, both during rehearsals and live performance [ 31 ], with an average exposure of 103 dB in PR versus 94 dB in CL PMs [ 27 ]; additionally, studies have described that PR PMs often play music without ear protection more commonly than CL PMs [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Music, at the both entertainment and professional level, can induce HL and other audiological symptoms such as tinnitus, hyperacusis, and diplacusis [ 9 , 26 ]; professional musicians (PMs) are exposed to high intensity sounds for a prolonged time during the day [ 27 ]. Many studies have focused on the prevalence of HL among PMs and the degree of hearing loss among them [ 28 , 29 , 30 ]; however, the extent to which the musical genre affects the risk of developing hearing loss in PM remains unclear [ 30 , 31 ]. Different music genres such as Pop/Rock (PR) or classical (CL) music entail different levels of noise exposure, which in turn depend on several factors including the type and number of instruments that are played at the same time and the intensity of the sound that is generated [ 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Audiological data have been published previously 10 . Clinical examinations were performed at the offices of Norsk Musikkråd in Oslo (musicians), and the Ear, Nose and Throat (ENT) department at the University Hospital of Northern Norway (controls).…”
Section: Methodsmentioning
confidence: 99%
“…In our study we conducted transient otoacoustic emissions (TEOAE) and pure-tone audiometry tests, these results are presented in a previously published article 10 . We were unable to detect a significant loss in TEOAE SNRs amongst rock musicians.…”
Section: Introductionmentioning
confidence: 99%
“…Τα δικά μας ευρήματα, και πιο συγκεκριμένα οι τιμές των SNR, συμφωνούν με τα ευρήματα των (Høydal et al, 2017).…”
Section: παροδικές ωτοακουστικές εκπομπές (τεοαε)unclassified